Morocco's Jobs Landscape : Identifying Constraints to an Inclusive Labor Market - Lopez-Acevedo, Gladys; Betcherman, Gordon; Khellaf, Ayache; Molini, Vasco (Washington, DC: World Bank, 2021)
This report sheds light on major labor market issues and challenges that Morocco faces. It is the first phase of the programmatic jobs program jointly undertaken with the government of Morocco. The report is a jobs diagnostic that analyzes microdata mainly from Labor Force Surveys and employs new analytical methods to identify the main trends in the labor market. The key challenges that emerge will provide the basis for a deeper analysis and policy formulation in the next phase of this program. "Morocco’s Jobs Landscape" identifies four priorities: accelerate structural transformation to create more and better jobs in higher-productivity sectors, encourage formalization and improve the quality of jobs, increase female labor force participation, and address youth inactivity and its long-term consequences. Morocco has made significant economic progress over the past 20 years, which has raised the living standards of its people. However, Morocco’s economic growth has not been labor-intensive enough to absorb its growing working-age population. It has had a low capacity to generate jobs, and the rate of job creation slowed after the 2008 financial crisis. Morocco is trying to overcome the “middle-income trap,” which has been preventing its convergence with more affluent middle-income countries. The government of Morocco has called for a new inclusive development model. The new model must address regional development imbalances, facilitate inclusion for youth and women, and continue to foster labor force skills upgrading. The COVID-19 pandemic and resultant safety measures have halted or slowed economic activity, which is worsening the labor market situation. The pandemic undoubtedly complicates prospects for jobs-led growth, and it will make the challenges highlighted in this report even more urgent and deserving of policy makers’ attention.